A New Synthesis of 2-Aminoindoles and 6-Aminopyrrolo[3,2-d]pyrimidines from π-Deficient 1,2-Dihaloarenes and Geminal Enediamines - Mishina, Maria S.; Ivanov, Alexander Yu.; Lobanov, Pavel S.; Dar’in, Dmitrii V. (Synthesis, 2016)
An efficient approach for the synthesis of fused 2-aminopyrroles via geminal enediamines and π-deficient 1,2-dihaloarenes is presented. The two-step methodology includes aromatic nucleophilic substitution of the activated halogen of dihaloarene with enediamine C-nucleophilic center followed by Cu-catalyzed intramolecular N-arylation. This approach allows access to a variety of 2-amino-6-nitroindoles and 6-aminopyrrolo[3,2-d]pyrimidines (including N-mono- and N,N-disubstituted) in moderate and good yields under mild conditions.
Keywords: 2-aminoindoles; pyrrolo[3,2-d]pyrimidines; geminal enediamines; cyclization; copper catalyst; N-arylation